Posttraumatic growth, rumination and coping strategies in children and adolescents exposed to the 2015 Coquimbo earthquake - Andrades, Mariela (2021)
The aim of the present study was to identify the coping strategies and ruminative styles that are related to Posttraumatic Growth (PTG), in a sample of 105 participants from 12 to 16 years old, surveyed 12 months after the 2015 earthquake in the city of Coquimbo, Chile. The results show that deliberate rumination and productive coping strategies significantly predicted PTG. In addition, it was observed that when participants feel significant threats to their integrity, their PTG levels increase. These results would allow designing intervention strategies that help to cope the consequences of a natural disaster in children and adolescents.